Early postoperative enteral nutrition and its impact on postoperative recovery in gastrointestinal tumor surgery - Weng, Peng-Hua; Du, Yan; Yuan, Feng (Frontiers in Oncology, 2025)
BackgroundSurgeries for gastrointestinal tumors frequently result in considerable postoperative complications, such as surgical site infections (SSIs) and impaired nutritional parameters. This study focuses on the role of Early Postoperative Enteral Nutrition (EPEN) in alleviating these difficulties.MethodsThis retrospective study included 110 patients undergoing gastrointestinal tumor surgery between January 2019 and January 2023. Patients receiving EPEN were allocated to the observation group, while others received conventional care. Nutritional indices (total protein [TP], albumin [ALB], and prealbumin [PA]) were measured at baseline and on postoperative day 14. Baseline inflammatory status, including C-reactive protein (CRP), procalcitonin (PCT), white blood cell (WBC) count, and derived ratios such as the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII), was also assessed. Clinical outcomes included wound healing time and postoperative complications.ResultsEPEN was associated with faster wound healing (10.32 ± 1.32 vs 13.65 ± 0.21 days; P<0.001) and a lower SSI rate (1.82% vs 17.02%; P = 0.015), with no difference in wound bleeding (5.45% vs 9.09%; P = 0.463). At day 14, TP, ALB, and PA were higher in the EPEN group (TP 70.76 ± 4.53 g/L; ALB 39.24 ± 1.87 g/L; PA 297.45 ± 21.32 mg/L; all P<0.001 vs control). Length of stay was similar (7.82 ± 1.21 vs 7.69 ± 1.59 days; P = 0.630). Time to first flatus (33.6 ± 5.8 vs 47.1 ± 7.1 hours; P<0.001), first bowel movement (55.2 ± 6.3 vs 70.5 ± 8.2 hours; P<0.001), and patient satisfaction (8.50 ± 1.10 vs 7.20 ± 1.30; P<0.001) favored EPEN.ConclusionsIn this retrospective study, EPEN might be associated with improvements in nutritional indicators and clinical outcomes, including faster wound healing and reduced surgical site infections in gastrointestinal tumor patients. However, the current data do not provide sufficient evidence to conclusively determine whether the improvements are directly due to EPEN, further prospective, randomized studies are needed to confirm these associations and clarify their causal relationships.